Mekanisme Kepercayaan Konsumen Digital: Integrasi Risiko dan Kemudahan Penggunaan terhadap Kontinuitas Transaksi di Shopee - Nur Ichsan (Genius: Jurnal Ekonomi Dan Manajemen, 2025)
This research is motivated by the increasing volume of digital transactions on the Shopee e-commerce platform which is not balanced with the stability of long-term consumer confidence, as well as the rampant mode of fraud and data leakage that strengthens the perception of risk among users. This research aims to test the mechanism of digital consumer trust through the integration of risk perception and ease of use on transaction continuity at Shopee. The type of research used is quantitative explanatory with a survey approach. The source of the research data is primary data obtained from 350 respondents of active Shopee users in Indonesia who have made at least three transactions in the last six months and have experience using the platform's security features. Sampling was carried out by purposive sampling and snowball sampling techniques. The results of the study show that digital consumer trust has a positive and significant influence on transaction continuity with a path coefficient of 0.487. Risk perception has a negative and significant effect on transaction continuity with a path coefficient of -0.342, as well as acting as a moderation variable that weakens the influence of trust on transaction continuity. Ease of use has a positive effect on transaction continuity both directly (0.215) and indirectly through trust mediation (0.201). This study concludes that transaction continuity at Shopee is determined simultaneously by trust as the main driver, risk perception as an inhibitor, and ease of use as multiple driving factors.